Preparation method of titanium oxide nano-composite metal electrode on surface of dielectric film for capacitor

By using vacuum evaporation technology to deposit titanium oxide nanocomposite metal electrodes on BOPP films, the problems of single composition, uneven distribution and limited self-healing ability of the existing metallized dielectric film electrodes are solved, and higher electrical performance and lower costs are achieved.

CN119542028APending Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411655371.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing metallized dielectric film electrodes have problems such as single electrode composition, uneven distribution, limited self-healing ability, poor wetting of the interface between the electrode and the dielectric film, and impure interface, resulting in poor electrical performance.

Method used

A method for preparing a titanium oxide nanocomposite metal electrode on the surface of a dielectric film for capacitors is adopted. A titanium metal layer is deposited on the BOPP film through vacuum evaporation technology, and a titanium oxide functional layer is formed on the surface of the film, and an aluminum electrode is evaporated on the titanium oxide functional layer to form a composite metal electrode.

Benefits of technology

It improves the flow capacity and self-healing performance of the metallized electrode, reduces square resistance, enhances interface binding force, reduces capacitance losses caused by the self-healing process, simplifies the process flow, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542028A_ABST
    Figure CN119542028A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a dielectric film surface titanium oxide nano composite metal electrode for a capacitor. A thermal evaporation method is adopted, metal titanium is used as an evaporation raw material, a continuous nano functional layer with chemical components close to those of titanium oxide can be deposited on a BOPP film under a non-vacuum condition, and the threshold thickness of a pure aluminum electrode can be reduced. On the premise of the same electrode thickness, the through-current capability of the metallized electrode is improved, and the adhesive force and the self-healing performance of the metal layer are obviously improved. Due to the high thermal conductivity and the high melting point of the titanium oxide functional layer, the lost electrode area of the composite electrode in a self-healing performance test is smaller, the composite electrode has the unique isolation self-healing characteristic, and capacitance loss caused by the self-healing process is reduced. Based on a traditional preparation method of vacuum evaporation of a capacitor manufacturer, the investment of pretreatment and other preparation cost is reduced, and the feasibility of the method applied to batch preparation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a metallized film electrode, in particular to a method for preparing a titanium oxide nano-composite metal electrode on the surface of a dielectric film for a capacitor. Background Art

[0002] Energy is a new technological hotspot in the development of contemporary society. In recent years, with the rapid development of various fields, the demand for high-performance dielectric capacitors has increased year by year, and at the same time, there is a desire for deeper research on their energy storage and electrical performance. As the main component of film capacitors, metallized dielectric film plays a decisive role in its performance, and the metallized electrode on the surface of the dielectric film is crucial to its special self-healing properties.

[0003] When metal oxides are deposited on the surface of polypropylene film, they will form a composite insulating medium with the polypropylene film. On the one hand, the relative dielectric constant of the composite film can be slightly improved, and at the same time, the thermal conductivity of the capacitor core can be improved, and the heat generated by dielectric loss or self-healing can be exported out of the capacitor as quickly as possible, preventing the dielectric film adjacent to the self-healing point from interlayer bonding, thus playing the role of isolation and self-healing. Interface modification has a significant effect on reducing the electrode threshold thickness, because the special interlayer interface structure introduced by it makes the material have better electrical properties.

[0004] In view of the above advantages of metal oxides as interface modification functional layers, combined with the research results of existing studies that reducing the evaporation rate can help generate oxides during the evaporation process to increase electrode adhesion, it is expected that the use of metal oxide interface modification methods can comprehensively improve the electrical and macroscopic properties of metallized films.

[0005] At present, some exploratory work has been carried out in the field of optoelectronic devices using metal oxides as dopants or insertion layers, but no relevant research has been reported in dielectric film metal electrode composites for capacitors. In addition, unlike the traditional evaporation process, the heterogeneous interface wettability obtained by acid pickling and plasma treatment is still poor, the interface bonding is very unstable, and even the surface of the polymer dielectric film is damaged and uneven, so that the electrical performance of the prepared metallized film is often greatly reduced compared with the expected design. Therefore, the metal electrode prepared on the dielectric film using the above scheme is a pure native interface structure formed under high-temperature evaporation conditions. In addition, the metal compound formed by oxidation also has excellent interface wettability and stable interface bonding with the aluminum electrode evaporated later. Compared with the method of coating and adding an interface layer, the interface bonding force is better; at the same time, the relevant evaporation process is optimized, and the composite coating that was originally only possible by sputtering coating is realized without changing the existing evaporation batch production line, reducing costs while avoiding the introduction of impurity phases such as sintering aids and the impact on material properties. Therefore, the present invention is an important innovation in the preparation of advanced nanocomposite dielectric film electrodes. Summary of the invention

[0006] The present invention aims to optimize the material types of existing metallized electrodes and overcome the problems existing in the preparation process. To this end, the purpose of the present invention is to propose a preparation method for a novel titanium oxide nanocomposite metal electrode on the surface of a dielectric film for capacitors, and to solve the technical problems existing in existing metallized dielectric film electrodes, such as single electrode composition, uneven distribution, limited self-healing ability, poor wettability of the interface between the electrode and the dielectric film, and impure interface.

[0007] To achieve the above object, the present invention adopts a solution of providing a method for preparing a titanium oxide nanocomposite metal electrode on the surface of a dielectric film for a capacitor, comprising the following steps:

[0008] Step 1: Before deposition, the rolled commercial BOPP film is ultrasonically cleaned with ethanol for 5 minutes and then transferred to the vacuum chamber of the thermal evaporation equipment.

[0009] Step 2: Then, titanium metal (purity: ≥99.999%) is used as a raw material, heated to a temperature higher than 1400° C., and a titanium metal layer is vacuum-evaporated on a BOPP film with a thickness of μm to obtain a first dielectric film.

[0010] Step 3: Reduce the vacuum degree of the vacuum chamber to normal pressure, so that the first dielectric film prepared in step 2 is exposed to oxygen, and after standing for 2 minutes, a titanium oxide functional layer is formed on the surface to obtain a second dielectric film.

[0011] Step 4: Then restore the high vacuum state of the vacuum chamber, use pure aluminum as the second evaporation source, heat the evaporation source to a temperature higher than 700°C, vaporize the metal aluminum therein, and evaporate it on the titanium oxide functional layer of the second dielectric film to obtain a titanium oxide nano-composite metal electrode on the surface of the dielectric film for the capacitor.

[0012] Furthermore, the evaporation temperature in step 2 is 1400° C., the evaporation temperature in step 4 is 700° C., the ambient temperature of the experimental process is room temperature, and the vacuum evaporation deposition process is carried out at room temperature.

[0013] Furthermore, the environment of the vacuum chamber in steps 2 and 4 should be maintained at a temperature better than 5×10 -4 Vacuum degree of Pa.

[0014] Furthermore, in the steps 2 and 4, the deposition rates of the metal titanium and aluminum are controlled at within the range.

[0015] Furthermore, the thickness of the titanium metal layer obtained by evaporation is 10nm-20nm, and the thickness of the aluminum electrode is 20nm.

[0016] As a second aspect, the present invention provides a titanium nano-composite metal electrode on the surface of a dielectric film for a capacitor prepared by the preparation method.

[0017] As a third aspect, the present invention provides a use of the titanium oxide nanocomposite metal electrode on the surface of the capacitor dielectric film in preparing a capacitor.

[0018] The beneficial effects of the present invention are as follows:

[0019] The traditional metallized dielectric thin film electrode has a single component, and the square resistance can only be improved by reducing the electrode thickness; the interface bonding force is poor, and the interface strength can only be increased by high-pollution and high-cost treatment methods; most of them can only be obtained by evaporation, but the final composition of the evaporated alloy or compound electrode cannot be guaranteed, and the complex composite electrode can only be obtained by sputtering and other methods, especially the self-healing performance as a key indicator of metallized film is very unsatisfactory and other related problems:

[0020] (1) Compared with the BOPP metallized film of pure aluminum electrode, the titanium oxide composite metallized electrode prepared by the present invention has lower square resistance and improved current flow capacity of the metallized electrode under the premise of the same thickness. The adhesion and self-healing performance of the metal layer are significantly improved. Due to the high thermal conductivity and high melting point of the titanium oxide functional layer, the composite electrode loses less electrode area in the self-healing performance test, has a unique "isolated self-healing" characteristic, reduces the capacitance loss caused by the self-healing process, and greatly improves its potential as an electrode material.

[0021] (2) The present invention realizes the preparation of a new composite electrode using commonly used thermal evaporation equipment based on the traditional process method, and directly performs metallization without pretreatment of the dielectric film, thereby simplifying the process flow, improving production efficiency, and reducing damage to the surface of the polymer film. In addition, the present invention can be put into production without major changes to the existing metallized film production line, greatly reducing equipment expenditure, and is energy-saving and environmentally friendly and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a process flow chart for preparing titanium oxide nanocomposite metal electrodes on the surface of dielectric films.

[0023] Figure 2 This is the square resistance curve of titanium oxide nanocomposite metal electrode on the surface of dielectric film with different component ratios and vapor deposition thickness.

[0024] Figure 3 The dielectric constant and energy storage density diagram of titanium oxide nanocomposite metal electrode on the surface of dielectric film with different composition ratios and vapor deposition thickness; among them, (a) is the dielectric constant diagram of nanocomposite metal electrode, and (b) is the dielectric loss.

[0025] Figure 4 This is a comparison chart of the self-healing performance of titanium oxide nanocomposite metal electrodes on the surface of dielectric films with different component ratios and vapor deposition thicknesses.

[0026] Figure 5 The transmission microscope morphology photographs of the titanium oxide nanocomposite metal electrode on the surface of the dielectric film prepared in Example 1 and the element distribution curve (TEM-EDS) at the interface, where (a) is the element distribution spectrum of the composite electrode cross section, and (b) is the content of different elements in the composite electrode cross section.

[0027] Figure 6 These are atomic force microscope images (AFM) of the titanium oxide nanocomposite metal electrode on the surface of the dielectric film prepared in Example 1, where (a) is a pure Al electrode, (a') is a height peak image, (b) is a titanium oxide composite electrode, and (b') is a height peak image.

[0028] Figure 7 This is the interface element depth distribution curve (AES) of the titanium oxide nanocomposite metal electrode on the dielectric film surface prepared in Example 1, where (a) is a pure Al electrode and (b) is a titanium oxide composite electrode.

[0029] Figure 8 This is a test curve of the interface bonding strength of the titanium oxide nanocomposite metal electrode on the surface of the dielectric film prepared in Example 1, wherein (a) is the scratch morphology, and (b) is a curve showing the variation of friction force with the scratch distance. DETAILED DESCRIPTION

[0030] The present invention is further described below with reference to the embodiments.

[0031] Example 1

[0032] (a) A rolled BOPP commercial film was cut into pieces of 35 × 35 mm in size, placed in an ultrasonic cleaner filled with anhydrous ethanol and cleaned for 5 min, and then dried.

[0033] (b) The film treated in step a is transferred to the vacuum chamber of the thermal evaporation equipment and the vacuum degree of the chamber is evacuated to be better than 5×10 -4 Pa, the titanium metal (purity: ≥99.999%) in the evaporating dish is heated to the evaporation temperature, during which the deposition rate of the titanium metal is controlled at Within the range, the thickness of the evaporated titanium metal layer is 20 nm.

[0034] (c) The vacuum degree of the vacuum chamber is reduced to normal pressure, and the BOPP dielectric film having a pure titanium metal layer on the surface obtained in step b is exposed to oxygen, and a titanium oxide film is formed on the surface after standing for 2 minutes.

[0035] (d) Restoring the high vacuum state of the vacuum chamber, using pure aluminum as the second evaporation source, heating the evaporation source to a temperature higher than 700° C. to vaporize the metal aluminum therein, and evaporating the aluminum electrode on the titanium oxide functional layer of the BOPP thin film with a titanium oxide layer obtained in step c. The thickness of the aluminum electrode is 20 nm, thereby obtaining a corresponding titanium oxide nanocomposite metal electrode on the surface of the dielectric film.

[0036] Example 2

[0037] (a) A rolled BOPP commercial film was cut into pieces of 35 × 35 mm in size, placed in an ultrasonic cleaner filled with anhydrous ethanol and cleaned for 5 min, and then dried.

[0038] (b) The film treated in step a is transferred to the vacuum chamber of the thermal evaporation equipment and the vacuum degree of the chamber is evacuated to be better than 5×10 -4 After Pa, the titanium metal (purity: ≥99.999%) in the evaporating dish is heated to the evaporation temperature, during which the deposition rate of the metal Ti is controlled at Within the range, the thickness of the evaporated titanium metal layer is 5 nm.

[0039] (c) The vacuum degree of the vacuum chamber is reduced to normal pressure, and the BOPP dielectric film having a pure titanium metal layer on the surface obtained in step b is exposed to oxygen, and a titanium oxide film is formed on the surface after standing for 2 minutes.

[0040] (d) Restoring the high vacuum state of the vacuum chamber, using pure aluminum as the second evaporation source, heating the evaporation source to a temperature higher than 700° C. to vaporize the metal aluminum therein, and evaporating the aluminum electrode on the titanium oxide functional layer of the BOPP thin film with a titanium oxide layer obtained in step c. The thickness of the aluminum electrode is 20 nm, thereby obtaining a corresponding titanium oxide nanocomposite metal electrode on the surface of the dielectric film.

[0041] Example 3

[0042] (a) A rolled BOPP commercial film was cut into pieces of 35 × 35 mm in size, placed in an ultrasonic cleaner filled with anhydrous ethanol and cleaned for 5 min, and then dried.

[0043] (b) The film treated in step a is transferred to the vacuum chamber of the thermal evaporation equipment and the vacuum degree of the chamber is evacuated to be better than 5×10 -4 Pa, the titanium metal (purity: ≥99.999%) in the evaporating dish is heated to the evaporation temperature, during which the deposition rate of the titanium metal is controlled at Within the range, the thickness of the evaporated titanium metal layer is 10 nm.

[0044] (c) The vacuum degree of the vacuum chamber is reduced to normal pressure, and the BOPP dielectric film having a pure titanium metal layer on the surface obtained in step b is exposed to oxygen, and a titanium oxide film is formed on the surface after standing for 2 minutes.

[0045] (d) Restoring the high vacuum state of the vacuum chamber, using pure aluminum as the second evaporation source, heating the evaporation source to a temperature higher than 700° C. to vaporize the metal aluminum therein, and evaporating the aluminum electrode on the titanium oxide functional layer of the BOPP thin film with a titanium oxide layer obtained in step c. The thickness of the aluminum electrode is 20 nm, thereby obtaining a corresponding titanium oxide nanocomposite metal electrode on the surface of the dielectric film.

[0046] Test Example 1

[0047] The titanium oxide nanocomposite metal electrode on the surface of the dielectric film prepared in the embodiment of the present invention was tested as follows:

[0048] 1) Using the thermal evaporation method, with metal Ti as the evaporation raw material, under non-vacuum conditions, a continuous nano-functional layer with a chemical composition close to titanium oxide can be deposited on the BOPP film. Through the square resistance test, it is found that the titanium oxide functional layer can reduce the threshold thickness of the pure Al electrode, such as Figure 2 shown.

[0049] 2) Compared with pure BOPP metallized film, titanium oxide composite metallized film has lower square resistance under the premise of the same thickness, which improves the current carrying capacity and dielectric constant of the metallized electrode. Figure 3The in-depth analysis of Auger electron spectroscopy revealed that significant interfacial diffusion occurred between Ti and the BOPP substrate during the coating process, which prevented the diffusion of Al in the film matrix.

[0050] 3) Nanoindentation testing found that the adhesion of the metal layer was significantly improved.

[0051] 4) Due to the high thermal conductivity and high melting point of the titanium oxide functional layer, the composite electrode loses less electrode area in the self-healing performance test, has a unique "isolated self-healing" characteristic, and reduces the capacitance loss caused by the self-healing process.

[0052] It should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Without making creative work, any modification, equivalent replacement, improvement, etc., shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a titanium oxide nanocomposite metal electrode on the surface of a dielectric film for a capacitor, characterized in that: The following steps are involved: The BOPP film is cleaned, pure titanium metal is used as a raw material, heated to a temperature higher than 1400° C., and a titanium metal layer is vacuum-evaporated on the BOPP film to obtain a first dielectric film; Under normal pressure, exposing the first dielectric film to oxygen and allowing it to stand to form a titanium oxide functional layer on the surface, thereby obtaining a second dielectric film; Under vacuum conditions, pure aluminum is heated to a temperature higher than 700° C. to vaporize the metal aluminum therein and deposit it on the titanium oxide functional layer of the second dielectric film to obtain a titanium oxide nanocomposite metal electrode on the surface of the dielectric film for a capacitor.

2. The method for preparing a titanium oxide nanocomposite metal electrode on the surface of a dielectric film for a capacitor according to claim 1, characterized in that: The cleaning is ultrasonic cleaning with ethanol for 5 minutes.

3. The method for preparing a titanium oxide nanocomposite metal electrode on the surface of a dielectric film for a capacitor according to claim 1, characterized in that: The vacuum condition is maintained at a vacuum degree better than 5×10 -4 Pa, the vacuum evaporation deposition process is carried out at room temperature, and the deposition rate of metal titanium and aluminum is controlled at within the range.

4. The method for preparing a titanium oxide nanocomposite metal electrode on the surface of a dielectric film for a capacitor according to claim 1, characterized in that: The purity of the pure metallic titanium is ≥99.999%.

5. The method for preparing a titanium oxide nanocomposite metal electrode on the surface of a dielectric film for a capacitor according to claim 1, characterized in that: The thickness of the titanium metal layer obtained by evaporation is 10nm-20nm, and the thickness of the aluminum electrode is 20nm.

6. A titanium nano-oxide composite metal electrode on the surface of a dielectric film for a capacitor prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the titanium oxide nanocomposite metal electrode on the surface of the capacitor dielectric film according to claim 6 in preparing a capacitor.